Analisis Kadar Vitamin C dan Tingkat Kesukaan pada Kulit Mochi dengan Substitusi Jambu Biji Merah (Psidium guajava L.): Analisis Kadar Vitamin C dan Tingkat Kesukaan pada Kulit Mochi dengan Substitusi Jambu Biji Merah (Psidium guajava L.) - Intan Ditya Prastanti; Farida Wahyu Ningtyias; Septy Handayani (Amerta Nutrition, 2026)
Background: The prevalence of anemia aged 15-24 years in Indonesia reached 15.5%, which is 18% in women and 14.4% in men according to the 2023 Indonesian Health Survey data. One of the efforts to help iron absorption is the consumption of blood supplement tablets along with vitamin C sources. Mochi is a semi-wet cake that is easily found in Indonesia. Mochi skin with red guava substitution is intended as an alternative source of vitamin C for the prevention of anemia in adolescent girls.Objectives: This study aimed to investigate eating habits and food preferences (with a focus on vegetables and snacks) among normal, overweight and obese of full-day school children in urban areas of Surabaya City.Methods: This type of research used quasi experimental with four modified formulas of red guava fruit puree substitution with the percentage of X0 (0%), X1 (45%), X2 (50%), X3 (55%). Furthermore, hedonic test was carried out on the level of liking by 35 panelists. The four formulas with three replications were laboratory tested for vitamin C content using Jacobs' method. Statistical test of vitamin C content was conducted with Kruskal Wallis and Mann Whitney U-Test. Statistical test of the level of favorability was carried out with Friedman test and Wilcoxon Sign Rank Test.Results: The average value of vitamin C content of X0, X1, X2, and X3 are 0.17 mg; 3.59 mg; 5.79 mg; and 7.95 mg. The best formula is mochi skin formula X2 (50% red guava puree substitution).Conclusions: Mochi skin with red guava substitution produced significant differences in taste, color, aroma, and texture as well as increased vitamin C levels when compared to the control formula. This product can be used as an alternative snack to help iron absorption as an effort to prevent anemia.